Responsive feeding education for parents with stunting babies aged 12-36 months - Irne Wida Desiyanti; Rakhmawati Agustina (Journal of Health Technology Assessment in Midwifery, 2022)
Background of Study: North Sulawesi Province becomes a province which has 31.4% of stunting cases. North Minahasa Regence becomes one of stunting local areas which are intervened in order to occur reduction cases which currently amounted to 29.7%. One of factors which affect stunting are mother’s knowledge which influence feeding practices. Responsive feeding is feeding practices which is recommended by WHO conducted with psychosocial approach. Responsive feeding effects on physical and mental development of babies. Mothers who live in stunting-prone area have lower responsive feeding knowledge and practice than those in non-stunting areas.Purpose of Study: for investigating the effect of feeding education with the concept of responsive feeding on the knowledge and practice of eating on stunting babies aged 12-36 months.Method of Study:  This study was quantitative study with experimental quasi approach. The study was conducted in Wori District, there were 11 people in case group and 7 people in control group. The respondent criteria were mothers who had stunting toddler aged 12-36 months and were not experiencing mental health. The analysis in this study used univariate and bivariate test. Pretest was provided before education was provided and post test was conducted 2 weeks after education.Result: Univariate test which is used is chi-square test and bivariate analysis is conducted through Independent Sample T-test. The finding of this study showed that there is enhancement of knowledge on case group after responsive feeding education is given however there is no enhancement in attitude. While in control group does not experience an enhancement both knowledge and attitude after education is given.Conclusion: Providing responsive feeding education can enhance mother’s knowledge about good feeding on stunting babies although it requires education for more than 2 weeks for increasing mother’s attitude in feeding of stunting babies.